VISUALISASI HADIS DALAM FILM CINTA DI PENGHUJUNG MALAM PADA CHANNEL YOUTUBE FILM MAKER MUSLIM - Luluk Atul Anisah; Homsanah, Aisahanis, Fatichatus Sa’diyah (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Development in this millennial era is dealing with the rapid pace of technology. There is a lot of content that begins to voice Islamic preaching either wrapped in short videos, quotes or films with Islamic nuances. One of the portraits of Islamic films is found on a youtube channel FMM (Muslim film maker) which has a vision to spread the value of goodness and positive values through its channel. The author has an interest in a series, namely the film love at the end of the night. In the series tells the background of students in college who struggle to find love at the end of the night, this raises a question then what is the concept of love that is justified in Islam and what religious values the film conveys to its viewers. Furthermore, the author will examine a Living Hadith Study based on da'wah media, which uses YouTube social media as its publication media, and analogises existing phenomena through visual signs that can be perceived by viewers of the film. The purpose of this study is to explore Hadith values and review the relevance of Hadith to the visualisation in the film. This research uses a qualitative method with a visual Living Hadith approach.